The Effect of Attitude, Normal Subjective and Perceived Behavioral Control (Pbc) on Actual Purchasing Through Purchases of Online Purchase in The Online Retail Industry - Anita Heptariza (Jurnal Ekonomi dan Bisnis Jagaditha, 2020)
Online shopping activities are currently growing. Online shopping activities are supported by the increasing number of Internet users. With the growing number of people who know the internet and along with the presence of Generation Z who was born in the digital age make the habit of spending goods and services slowly but surely have to switch online. One of the factors that affect online shopping is the intention of purchasing online. Theory of Planned Behavior (TPB) explains that consumer behavior is shaped by attitudes, subjective norms, and perceived behavioral control (PBC) that form the intention of online purchasing. This study aims to analyze the effect of attitudes on online purchase intentions, to analyze the effect of subjective norms on online purchasing intentions, to analyze the effect of PBC on online purchase intentions and to analyze the effect of online purchase intentions on actual purchases. The research was conducted at Prama Sanur Beach Hotel. The technique of data collection used are observation, interview, documentation, questionnaires. Data analysis technique using quantitative analysis with PLS program. The results show that attitudes have a positive and significant influence on the intentions of online purchasing. Subjective norms have a positive but insignificant effect on online purchase intentions. Perceived Behavioral Control (PBC) has a positive and significant effect on online purchasing intentions, and online purchase intentions have a positive and significant effect on actual purchases.